Effects of adding soybean waste on growth performance and carcass quality in quails - Mohd Azmi, Amirul Faiz; Wan Roslan, Wan Nur Hanani; Zulkifli Amin Rashid, Athirah Zawani; Mohd Hafiz Ngoo, Siti Aisyah; Mohd Noor, Mohd Hezmee; Rashid, Muhammad Azrolharith; Saad, Mohd Zamri; Nur Adli, Danung; Abu Hassim, Hasliza (ResearchersLinks Ltd, 2023)
This study determined the effects of feeding soybean waste at different levels on the growth performance and carcass quality in quails (Coturnix coturnix). Forty-five male broiler quails aged two-days-old were reared for three weeks before they were used for the experiment. At the start of the experiment, the quails were divided into 3 groups of 15 quails per group. Group 1 (T0) was treated with 100 commercial diet without soybean waste, Group 2 (T1) was treated with 15 soybean waste + 85 commercial diet, and Group 3 (T2) was treated with 30 soybean waste + 70 commercial diet. For growth performance, the body weight and average daily gain were measured. Meat qualities were evaluated based on the dressing weight, pH, and meat proximate analysis. The results revealed that the body weight, average daily gain, dressed weight and pH value were significantly differ (p